Anisotropic slip activation via homogeneous dislocation nucleation in ZrB2 ceramic grains during nanoindentation. (15th July 2018) - Csanádi, Tamás; Naughton-Duszová, Annamária; Dusza, Ján
Abstract: Anisotropic dislocation nucleation of differently oriented zirconium diboride (ZrB2 ) grains in a polycrystalline ZrB2 -based ceramic composite was investigated during nanoindentation with a Berkovich tip. Based on the Hertzian stress analysis of the measured strain bursts, the critical resolved shear stresses for slip systems of 10 1 ¯ 0 11 2 ¯ 0, 10 1 ¯ 0 0001 and 10 1 ¯ 0 11 2 ¯ 3 types were determined. Homogeneous dislocation nucleation was revealed with near theoretical critical resolved shear stress (~35 GPa) for each slip system. The analysis of the orientation dependence of the calculated maximal resolved shear stress values inferred anisotropic dislocation nucleation in ZrB2 grains with single and simultaneous activation of the investigated slip systems. Graphical abstract: Unlabelled Image